SANITASI ALERGEN PADA PROSES PRODUKSI BISKUIT DALAM UPAYA MENGURANGI RESIDU ALERGEN TELUR - Kartika Sari; Nurheni Sri Palupi; Puspo Edi Giriwono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2021)
Food allergy is a hypersensitive response to food, generally protein, triggered by body immune system. These responses can be mild, however in very rare cases may cause severe reactions and life threatening known as called anaphylaxis. Food allergy has been one of the main factors for product recall. It can happen due to many reasons, such as product package labeling fault, raw material labeling fault and cross contamination. Validation of the effectiveness of cleaning and sanitation process become a critical point to minimize cross contamination. This study aimed to determine the optimum chemical concentration and contact time to eliminate egg residue in biscuit production cleaning process, obtain valid and verified cleaning procedures, and produce cleaning procedures that can be implemented in a production line. The result showed that physical cleaning/pre-cleaning for 30 minute and using 1% (v/v) concentration of caustic based polybrite chemical cleaning for 3-minute contact time can effectively eliminate the egg residue on stainless steel and polyurethane surface equipment. Food contact surface material and product characteristics (wet dough, dry biscuit) affected the number of egg residue on the equipment. Packing area with food contact surface equipment made from stainless steel is not considered critical area for allergen sanitation. It is shown that prior to sanitation process, analysis of egg allergen residue has already given negative result. Validation process can prove the effectiveness of allergen sanitation process to prevent potential egg allergen cross contamination in biscuit production.